PENINGKATAN PENETASAN TELUR IKAN KOKI (Carassius auratus) MENGGUNAKAN ECENG GONDOK (Pontederia crassipes) PADA PEMIJAHAN INDUK - Rizmauliana, Fadila; Waluyo, Waluyo; Tartila, Shobrina Silmi Qori (Universitas Teuku Umar, 2023)
Goldfish (Carassius auratus) is a type of ornamental fish with various body shapes and colors. Goldfish in Indonesia are classified as high-economic fish, because they are in great demand by the public, especially ornamental fish hobbyists. The demand for goldfish is quite high, it is necessary to increase the goldfish hatchery activities so that the supply of seeds can be fulfilled with good quality and quantity. This scientific article aimed to describe the goldfish hatchery techniques and discover the obstacles in goldfish hatchery activities. This activity was carried out on 26 December 2022 – 30 January 2023 at BPPP Tegal, Central Java. Goldfish hatchery techniques include preparation of spawning facilities, parent selection, broodstock rearing, broodstock spawning, egg hatching, and water quality control. The fertilization rate of the oranda goldfish is 97%, the hatching rate of the oranda goldfish is 91.79%, the survival rate of the larvae of the oranda goldfish is 60.25% and the survival rate of the seeds of the oranda goldfish is 59.46%. The temperature during the breeding activity is 24-33°C, DO at 4-11 mg/l, pH at 6-8, and ammonia at 0-0.25 mg/l. Water quality at the breeding site is good and optimal for goldfish hatchery activities. Water quality control is usually performed by changing the water by 50% of the pond height.